Environmental controls of frost cracking revealed through in-situ acoustic emission measurements in steep bedrock - Girard, Lucas; Gruber, Stephan; Weber, Samuel; id_orcid:0 000-0003-0720-5378; Beutel, Jan; id_orcid:0 000-0003-0879-2455 (Geophysical Research Letters, 2013)
ISSN:0094-8276 ISSN:1944-8007